Effect of organic fraction of municipal solid waste addition to high rate activated sludge system for hydrogen production from carbon rich waste sludge - Tunay, Dogukan; Yildirim, Oznur; Ozkaya, Bestami; Demir, Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Municipal solid waste has been used for bio-methane production for many years. However, both methane and carbon dioxide that is produced during bio-methanization increases the greenhouse gas emissions; therefore, hydrogen production can be one of the alternatives for energy production from waste. Hydrogen production from the organic substance was studied in this study with the waste activated sludge from the municipal wastewater treatment. High rated activated sludge (HRAS) process was applied for the treatment to reduce energy consumption and enhance the organic composition of WAS. The highest COD removal (76%) occurred with the 12 g/L organic fraction of municipal solid waste (OFMSW) addition at a retention time of 120 min. The maximum hydrogen and methane yields for the WAS was 18.9 mL/g VS and 410 mL/g VS respectively. Total carbon emission per g VS of the substrate (OFMSW thorn waste activated sludge) was found as 0.087 mmol CO2 and 28.16 mmol CO2 for dark fermentation and bio-methanization respectively. These kinds of treatment technologies required for the wastewater treatment plantcompensate it some of the energy needs in a renewable source. In this way, the HRAS process decreases the energy requirement of wastewater treatment plant, and carbon-rich waste sludge enables green energy production via lower carbon emissions. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Bio-hydrogen; High rate activated sludge; Dark fermentation; Waste sludge; ANAEROBIC CO-DIGESTION; METHANE PRODUCTION; WATER TREATMENT; FOOD WASTE; BIOHYDROGEN PRODUCTION; SEWAGE-SLUDGE; GROWTH; FERMENTATION; DEGRADATION; RECOVERY; Chemistry; Electrochemistry; Energy & Fuels